Respuesta :
Answer:
r = 24
Step-by-step explanation:
3(r+2)+5(2−r)=−32
Step 1: Simplify both sides of the equation.
3(r+2)+5(2−r)=−32
(3)(r)+(3)(2)+(5)(2)+(5)(−r)=−32(Distribute)
3r+6+10+−5r=−32
(3r+−5r)+(6+10)=−32(Combine Like Terms)
−2r+16=−32
−2r+16=−32
Step 2: Subtract 16 from both sides.
−2r+16−16=−32−16
−2r=−48
Step 3: Divide both sides by -2.
−2r/-2 = -48/-2
r = 24
Answer: r = 24
3(r+2)+5(2-r) =-32
this equals (if we do the multiplication)
3r+6+10-5r=-32
this equals (if we simplify)
-2r+16=-32
this equals (because we are subtracting from 1 side, we must subtract from the other)
-2r=-48
r=24